Menata Bahasa, Merawat Keberagaman: Kajian Dokumen Rpph/Modul Ajar Paud Berbasis Bahasa Inklusif - Miratul Hayati Miratul Hayati; Nadylla Tri Sukmawati (Universitas Muhammadiyah Metro, 2026)
This study examines three PAUD (Early Childhood Education) Daily Lesson Plan/Teaching Module (RPPH/Modul Ajar) documents using an inclusive language lens to assess how curricular discourse promotes learning equity for young children. Qualitative document analysis with a thematic approach was employed, focusing on four analytical dimensions: gender representation and anti‑stereotyping practices; instructional tone and the degree of autonomy‑supportive language; the developmental appropriateness of scientific terminology for early language development; and differentiation strategies, including the application of Universal Design for Learning (UDL). The results show that several lesson plans continue to reproduce gender dichotomies, rely heavily on directive instructional formulations, and introduce abstract concepts without consistent multimodal scaffolding. In addition, UDL principles are not articulated explicitly, and accommodations for children requiring additional learning support or for multilingual learners remain limited. These findings align with previous studies on early childhood gender socialization, autonomy‑supportive pedagogy, Developmentally Appropriate Practice, and the contribution of UDL to inclusive learning. The study recommends revising curricular language to be more affirmative, developmentally responsive, and sensitive to children’s diversity, and systematically integrating UDL. As a practical contribution, this study provides concrete guidance for teachers and curriculum developers in Indonesia to design RPPH that are more inclusive, sensitive to diversity, and supportive of equitable learning from an early age.